A Plasma Cell Myeloma With Post-Therapy Anaplastic Morphology, Osteomyelosclerosis, and Strong Pan-Cytokeratin (AE1/AE3) Expression: A Potential Diagnostic Pitfall. (May 2018) - Bharani, Vani; Sharma, Prashant; Bal, Amanjit; Prakash, Gaurav
Reactive and neoplastic plasma cells can display considerable morphological anaplasia as well as variable immunoreactivity for epithelial markers including epithelial membrane antigen, pan-cytokeratin (panCK) and high-molecular-weight cytokeratin, potentially creating diagnostic dilemmas. We describe the case of a 51-year-old male, previously treated for IgGλ plasma cell myeloma, whose bone marrow biopsy showed focal replacement by sheets of pleomorphic malignant cells and grade 3 myelofibrosis, raising the morphological possibility of a carcinomatous infiltration. First-line immunohistochemistry revealed strong panCK as well as CD138 positivity. However, subsequent MUM-1 and CD38 stains were also positive, clinching the diagnosis of relapsed plasma cell myeloma with anaplastic morphology and aberrant strong cytokeratin expression. The case warns of the perils of using limited immunohistochemical panels in poorly differentiated metastatic neoplasms and the importance of providing a complete clinical background to the reporting pathologist.